Associations between an IgG3 polymorphism in the binding domain for FcRn, transplacental transfer of malaria-specific IgG3, and protection against Plasmodium falciparum malaria during infancy: A birth cohort study in Benin. - Dechavanne, Célia; Dechavanne, Sébastien; Sadissou, Ibrahim; LOKOSSOU, GATIEN; Alvarado, Fernanda; Dambrun, Magalie; MOUTAIROU, KABIROU; COURTIN, David; Nuel, Gregory; Garcia, André; Migot-Nabias, Florence; King, L Christopher (My University, 2017)
Background Transplacental transfer of maternal immunoglobulin G (IgG) to the fetus helps to protect against malaria and other infections in infancy. Recent studies have emphasized the important role of malaria-specific IgG3 in malaria immunity, and its transfer may reduce the risk of malaria in infancy. Human IgGs are actively transferred across the placenta by binding the neonatal Fc receptor (FcRn) expressed within the endosomes of the syncytiotrophoblastic membrane. Histidine at position 435 (H435) provides for optimal Fc–IgG binding. In contrast to other IgG subclasses, IgG3 is highly polymorphic and usually contains an arginine at position 435, which reduces its binding affinity to FcRn in vitro. The reduced binding to FcRn is associated with reduced transplacental transfer and reduced half-life of IgG3 in vivo. Some haplotypes of IgG3 have histidine at position 435. This study examines the hypotheses that the IgG3-H435 variant promotes increased transplacental transfer of malaria-specific antibodies and a prolonged IgG3 half-life in infants and that its presence correlates with protection against clinical malaria during infancy. Methods and findings In Benin, 497 mother–infant pairs were included in a longitudinal birth cohort. Both maternal and cord serum samples were assayed for levels of IgG1 and IgG3 specific for MSP119, MSP2 (both allelic families, 3D7 and FC27), MSP3, GLURP (both regions, R0 and R2), and AMA1 antigens of Plasmodium falciparum. Cord:maternal ratios were calculated. The maternal IgG3 gene was sequenced to identify the IgG3-H435 polymorphism. A multivariate logistic regression was used to examine the association between maternal IgG3-H435 polymorphism and transplacental transfer of IgG3, adjusting for hypergammaglobulinemia, maternal malaria, and infant malaria exposure. Twenty-four percent of Beninese women living in an area highly endemic for malaria had the IgG3-H435 allele (377 women homozygous for the IgG3-R435 allele, 117 women heterozygous for the IgG3-R/H alleles, and 3 women homozygous for the IgG3-H435 allele). Women with the IgG3-H435 allele had a 78% (95% CI 17%, 170%, p = 0.007) increased transplacental transfer of GLURP-R2 IgG3 compared to those without the IgG3-H435 allele. Furthermore, in infants born to mothers with the IgG3-H435 variant, a 28% longer IgG3 half-life was noted (95% CI 4%, 59%, p = 0.02) compared to infants born to mothers homozygous for the IgG3-R435 allele. Similar findings were observed for AMA1, MSP2-3D7, MSP3, GLURP-R0, and GLURP-R2 but not for MSP119 and MSP2-FC27. Infants born to women with IgG3-H435 had a 32% lower risk of symptomatic malaria during infancy (incidence rate ratio [IRR] = 0.68 [95% CI 0.51, 0.91], p = 0.01) compared to infants born to mothers homozygous for IgG3-R435. We did not find a lower risk of asymptomatic malaria in infants born to women with or without IgG3-H435. Limitations of the study were the inability to determine (i) the actual amount of IgG3-H435 relative to IgG-R435 in serum samples and (ii) the proportion of malaria-specific IgG produced by infants versus acquired from their mothers. Conclusions An arginine-to-histidine replacement at residue 435 in the binding domain of IgG3 to FcRn increases the transplacental transfer and half-life of malaria-specific IgG3 in young infants and is associated with reduced risk of clinical malaria during infancy. The IgG3-H435 allele may be under positive selection, given its relatively high frequency in malaria endemic areas.
Keywords: IgG3; polymorphism; Plasmodium falciparum; FcRn; infancy; protection